2021
DOI: 10.3389/fmars.2021.689280
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Workflow Based on the STAVIRO Unbaited Underwater Video System for Monitoring Fish and Habitat Essential Biodiversity Variables in Coastal Areas

Abstract: Essential Biodiversity Variables (EBV) related to benthic habitats and high trophic levels such as fish communities must be measured at fine scale but monitored and assessed at spatial scales that are relevant for policy and management actions. Local scales are important for assessing anthropogenic impacts, and conservation-related and fisheries management actions, while reporting on the conservation status of biodiversity to formulate national and international policies requires much broader scales. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Video surveys have been used extensively throughout marine research as an automated alternative to diver-led VCS to monitor fish abundance and diversity, while also allowing for extrapolation of behaviour. 35,[107][108][109][110] Video surveying continues to improve as more capable cameras become available and new configurations are tested to increase the amount of water column surveyed. Baited remote underwater video systems (BRUVs) are commonly used in biological surveying and involves baiting a camera with food items to lure in any fish or macroinvertebrate in the area for video capture.…”
Section: Underwater Videomentioning
confidence: 99%
See 2 more Smart Citations
“…Video surveys have been used extensively throughout marine research as an automated alternative to diver-led VCS to monitor fish abundance and diversity, while also allowing for extrapolation of behaviour. 35,[107][108][109][110] Video surveying continues to improve as more capable cameras become available and new configurations are tested to increase the amount of water column surveyed. Baited remote underwater video systems (BRUVs) are commonly used in biological surveying and involves baiting a camera with food items to lure in any fish or macroinvertebrate in the area for video capture.…”
Section: Underwater Videomentioning
confidence: 99%
“…109,113 A study comparing the latter design to a traditional BRUV observed a significant increase in previously cryptic species and up to 60% higher abundance estimates of schooling species. 113 Unbaited 360 rotating cameras have also shown promise to provide more accurate estimation of ecological metrics than do traditional BRUVs, 107 and using parallel cameras may give a better representation of both biomass and swim speed. 114 Semi-automation of data processing could allow for larger temporal datasets to be efficiently analysed to measure how assemblages change over time.…”
Section: Underwater Videomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because recording occurs over a 360 • field of view, fishes and habitats may be quantified over an estimated surface area around the lander. The STAVIRO protocol has proved efficient and reliable with over 5000 valid deployments in varied habitats of both temperate and tropical coral reef ecosystems since 2007 [6]. These contributed to numerous assessments of biodiversity and fished resources in the Pacific, Indian, and Atlantic oceans and in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%